1976
DOI: 10.1002/chin.197637158
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: CYCLIC UNSATURATED COMPOUNDS. LIX. ACETOXYCYCLOPENTADIENE

Abstract: Aus dem Acetoxydicyclopentadien (I) entsteht bei 185‐195°C unter Cyclopentadien‐Eliminierung ein Gemisch isomerer Diacetoxydicyclopentadiene (II); die Depolymerisation dieses Dimerengemisches bei 400°C (im Quarz‐Rohrreaktor) liefert ein 1:3‐Gemisch der Acetoxycyclopentadien‐Isomeren (III) und (IV).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1991
1991
1991
1991

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The adduct was symmetrical, i.e., it was derived from 7 and not from 8. 4 Irradiation of the methyl singlet in the 'H nmr resulted in a significant nOe of the signal due to the protons a to the carbonyls, and vice versa. Thus, the structure of the adduct could only have been 9, the product of endo addition, anti to the oxygen.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The adduct was symmetrical, i.e., it was derived from 7 and not from 8. 4 Irradiation of the methyl singlet in the 'H nmr resulted in a significant nOe of the signal due to the protons a to the carbonyls, and vice versa. Thus, the structure of the adduct could only have been 9, the product of endo addition, anti to the oxygen.…”
Section: Resultsmentioning
confidence: 99%
“…Double dehydrobromination was effected with DBU. The 'H nmr of the product displayed a single set of signals, but Vogel and Giinther (13) demonstrated that this is really an average of the signals of benzene oxide (3) and its valence tautomer, oxepin (4). The addition of N-phenylmaleimide to an ether solution of the tautomeric mixture resulted in smooth conversion to a single adduct.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation